Added value of including waves into a coupled atmosphere–ocean model system within the North Sea area - Grayek, Sebastian; Wiese, Anne; Ho-Hagemann, Ha Thi Minh; Staneva, Joanna (Frontiers in Marine Science, 2023)
In this study, the effects of fully coupling the atmosphere, waves, and ocean compared with two-way-coupled simulations of either atmosphere and waves or atmosphere and ocean are analyzed. Two-year-long simulations (2017 and 2018) are conducted using the atmosphere–ocean–wave (AOW) coupled system consisting of the atmosphere model CCLM, the wave model WAM, and the ocean model NEMO. Furthermore, simulations with either CCLM and WAM or CCLM and NEMO are done in order to estimate the impacts of including waves or the ocean into the system. For the North Sea area, it is assessed whether the influence of the coupling of waves and ocean on the atmosphere varies throughout the year and whether the waves or the ocean have the dominant effect on the atmospheric model. It is found that the effects of adding the waves into the system already consisting of atmosphere and ocean model or adding the ocean to the system of atmosphere and wave model vary throughout the year. Which component has a dominant effect and whether the effects enhance or diminish each other depends on the season and variable considered. For the wind speed, during the storm season, adding the waves has the dominant effect on the atmosphere, whereas during summer, adding the ocean has a larger impact. In summer, the waves and the ocean have similar influences on mean sea level pressure (MSLP). However, during the winter months, they have the opposite effect. For the air temperature at 2 m height (T_2m), adding the ocean impacts the atmosphere all year around, whereas adding the waves mainly influences the atmosphere during summer. This influence, however, is not a straight feedback by the waves to the atmosphere, but the waves affect the ocean surface temperature, which then also feedbacks to the atmosphere. Therefore, in this study we identified a season where the atmosphere is affected by the interaction between the waves and the ocean. Hence, in the AOW-coupled simulation with all three components involved, processes can be represented that uncoupled models or model systems consisting of only two models cannot depict.